Legal Analisis Of Judge Consideration In Settlement Of Divorce Decision Case (Study Of Baubau Pa Decision Number 0298/Pdt/2019/Pa.Bb) - Suhartono, Rizki Mustika; Mashendra, Mashendra; Muh. Karim, La Ode; Sariati, Sariati; Ar-Rayyan, Hayatul Jannah (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to determine: to know and examine how judges consider in the settlement of divorce divorce cases. The research method used in Ziniz's research is Empirical Normative Law research. Legal research is a research method that seeks to find the law in the law that is actually or should be, examines how the law works in society, then uses research methods, the quality of the method. The collection of data and information was carried out at the Bau-Bau Religious Court. The second stage used in this research consists of: Primary, secondary and tesier legal instruments. Depending on the nature of the research and the research material, all available information will be carefully analyzed, with the help of which the collected data are sorted according to their categories and explained in the search for answers to research questions. By using the reduction method, conclusions are drawn from the prepared data and research results.The judge's consideration in deciding the decision on parental responsibility is very appropriate by considering the income of the parents based on the evidence brought before the trial.